Engineering bispecific T-cell engagers to deplete eosinophils for the treatment of severe eosinophilic asthma - Kim, Jun Ho; Kim, Dae Seong; Park, Hae Sim; Kim, Yong Sung (Clinical Immunology, 2023)
Severe eosinophilic asthma (SEA) is characterized by elevated eosinophil counts in the blood and airway mucosa. While monoclonal antibody therapies targeting interleukin-5 (IL-5) and its receptor (IL-5Rα) have improved treatment, some patients remain unresponsive. We propose an alternative approach to eliminate eosinophils using T cells by engineering IL-5Rα × CD3 bispecific T-cell engagers (bsTCEs) that target both IL-5Rα on eosinophils and CD3 on T cells. We designed different formats of IL-5Rα × CD3 bsTCEs, incorporating variations in valency, geometry, and affinity for the target antigen binding. We identified the single-chain variable fragment (scFv)-Fc format with the highest affinity toward the membrane-proximal domain of IL-5Rα in the IL-5Rα-binding arm showed the most potent cytotoxicity against IL-5Rα-expressing peripheral eosinophils by activating autologous primary T cells from healthy donors. This study proposes IL-5Rα × CD3 bsTCEs as potential alternatives for SEA treatment. Importantly, it demonstrates the first application of bsTCEs in eliminating disease-associated cells, including eosinophils, beyond cancer cells.
Keywords: Antibodies, Monoclonal; Asthma; Eosinophils; Humans; T-Lymphocytes; Bispecific T cell engager; Eosinophils; IL-5 receptor alpha; Severe eosinophilic asthma; T-cell dependent cytotoxicity